PENGARUH PROGRAM KETERAMPILAN TATA BUSANA TERHADAP MINAT BERWIRAUSAHA PADA PESERTA DIDIK DI MAN 2 MADIUN - Rosemala Rusmadinar; Peppy Mayasari (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The high unemployment rate among high school graduates demands that formal educational institutions take an active role as entrepreneurial incubators. The provision of relevant vocational skills has become crucial in fostering entrepreneurial interest. This study aims to measure and analyze in depth the influence of the fashion sewing skills program on the formation of entrepreneurial interest among students at MAN 2 Madiun. This research employs a descriptive quantitative approach. Sampling was conducted using a saturated sampling technique (total sampling), involving 25 students who actively participated in the fashion skills program. Primary data were collected through a closed-ended Likert-scale questionnaire instrument that had passed validity and reliability tests. Data processing was analyzed using classical assumption prerequisite tests, followed by simple linear regression analysis. The factual results of the study indicate that the implementation level of the skills program falls into the very good category (84% of students are motorically skilled). Accordingly, entrepreneurial interest is also classified as high (88%). Hypothesis testing (t-test) obtained a significance probability value of 0.000 < 0.05, which confirms a positive and significant influence. The magnitude of the contribution of fashion skills to entrepreneurial interest, based on the coefficient of determination test, reached 42.4%, while the remaining 57.6% is influenced by external factors outside this research model. In conclusion, mastery of technical skills such as sewing is proven effective in strengthening behavioral control and fostering students' self-confidence to dare to initiate economic independence and establish independent businesses in the future.